Characterizations of novel broad-spectrum lytic bacteriophages Sfin-2 and Sfin-6 infecting MDR Shigella spp. with their application on raw chicken to reduce the Shigella load - Ahamed, S. K. Tousif; Rai, Srijana; Guin, Chiranjib; Jameela, Rameez Moidu; Dam, Somasri; Muthuirulandi Sethuvel, Dhiviya Prabaa; Balaji, V.; Giri, Nabanita (Frontiers in Microbiology, 2023)
The evidence and prevalence of multidrug-resistant (MDR) Shigella spp. poses a serious threat globally to public health and economic concerns. Food or water born MDR Shigella spp. demands an alternate strategy to counteract this threat. In this regard, phage therapy drew great interest from medical practitioners and researchers as a potential way to combat MDR pathogens. In this observation, we isolated Shigella phages from environmental water samples against clinically isolated different MDR Shigella spp .In the current work, we have defined the isolation, and detailed physical and genomic characterizations of two phagesSfin-2 and Sfin-6 from environmental water samples. The phages exhibited potent lytic activity against Shigellaflexneri, Shigelladysenteriae, Shigellasonnei and showed absorption within 5-10 min, burst size of ~74 to ~265 PFU/cell, and a latent period of 5-20 min. The phages were stable at a broad pH range and survived an hour at 50°C. The purified phage Sfin-2 and Sfin-6 belong to the family Siphoviridae with an isometric head (64.90 ± 2.04 nm and 62.42± 4.04 nm respectively) and a non-contractile tail (145 ± 8.5 nm and 148.47 ± 14.5 nm respectively).Insilico analysis concluded that the size of the genomic DNA of phage Sfin-2 is 50,390 bp with a GC content of 44.90% while phage Sfin-6 genome size is 50,523 bp with a GC content of 48.30 %. The phage Sfin-2 have 85 and Sfin-6 have 83 putative open reading frame (ORFs) A total of 85 and 83 putative open reading frames (ORFs) were predicted in the phage Sfin-2 and Sfin-6 respectively. Furthermore, comparative genomic and phylogenetic analysis revealed that both phages represented different isolates and novel members of the T1-like phages. Phage Sfin-2 and Sfin-6 either individually or in cocktail form showed a significant reduction in viable Shigella count on raw chicken samples after 72 h of incubation. Therefore these results indicate that these phages might have a potential role in therapeutic approaches for shigellosis patients as well as in biological control of MDR Shigella spp. in the poultry or food industry during the course of meat storage.